LibAx a JDBC-compliant library database system on the web - Amarille, Pamela; Escober, Clarence; Lingad, Edwin; Ng, Elijah; Sy, Stephanie (1996)
Libax is a library search engine on the World Wide Web that aims to ease searching and retrieving of information. It allows users to enter keyword searches on documents like abstracts, dissertation, research and term papers. An extension of the project is to provide access to a multi-media library database containing image, video and sound files. All the user needs is a browser and a connection to the Internet/Intranet to access our system.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Web search engines; LibAx (Computer program).; library database system